Emschermannia ramificata—a new genus and species of solitary entoproct from the Kara Sea, Russia - Borisanova, Anastasia O. (Zootaxa, 2016)
A new genus and species of solitary entoproct, Emschermannia ramificata, is described from the Kara Sea. It is an epibiont of the nephtyid polychaete Aglaophamus malmgreni, collected from 25–472 m depth. The species is about 250–300 μm long, with 8–10 tentacles, and buds are formed from a frontal area of the calyx. The calyx and stalk are not separated from each other by a cuticular septum, and a star-cell complex is absent. Emschermannia ramificata attaches to a substratum via a basal plate from which pseudostolons grow. Zooidal morphology conforms to that of the Loxosomatidae, but the attachment structure is unique among solitary entoprocts; it resembles basal plates and stolons of colonial entoprocts, but pseudostolons of Emschermannia serve only for attachment, not for budding. Overall, the morphology of Emschermannia may be considered intermediate between that of solitary and colonial forms, with relevance to evolutionary development within Entoprocta.